Pathways to excellence developing and cultivating leaders for the classroom and beyond - Lahera, Antonia Issa.; Hamdan, Kamal; Normore, Anthony H. (Bingley, U.K. : Emerald, 2014)
Pathways to excellence : developing and cultivating leaders for the classroom and beyond examines how leadership and layers of leaders are developed and cultivated from the classroom to the boardroom. A wide body of research exists that focuses on specific educational leadership development and training programs. Evidence of being ready to lead upon program completion and performance post preparation is less available. Scant attention has been paid to programs that prepare leaders in different layers of an organization to not only become individually high performing but to also work collaboratively to create great schools. The book contends that the principal cannot effectively lead a school alone - other key players are critical. The editors have cast a wide net of respected contributors from various levels of organizational school leadership and specialties including traditional schools, charter schools, teacher education, district level leadership, special education, master teacher leadership, university and college level leadership. Implications for theory and practice will be discussed as it relates to leadership development and preparation of key players and constituents.
The department chair : a conundrum of educational leadership versus educational management / Anthony H. Nomore, Jeffrey S. Brooks -- Dispositions matter! Now what? Exploring leader dispositions, measurement, and practical applications for helping school leaders to grow / Leslie Hazle Bussey, Jennie Welch -- The vice principalship : the forgotten realm / Heather M. Rintoul, Richard Kennelly -- How to love change and lead it / Kendall Zoller -- Research-based instructional strategies in the classroom : the missing link in the school improvement process / Dennis S. Fox -- Ready to lead : creating a pathway that ensures readiness / Antonia Issa Lahera, Stefanie Holzman, Pamela Robinson -- The unique aspects of high performing school leaders / Pete Pillsbury -- Grounded in practice : designing & implementing relevant and student centered curriculum / H. Orletta Nguyen -- The CASLA chorus : leader's voices in the field / Roberta Benjamin-Edwards -- Providing effective special education teachers in low-income urban settings : implications for educational leadership / Mary C. Esposito, Kamal Hamdan, Xiomara Benitez -- Recruitment, selection, placement, and support in the preparation of quality of urban secondary teachers / Kamal Hamdan ... [et al.] -- The development of the teacher leader through the TTT lab school / Kamal Hamdan, Cecilia Dueñas, James Borden -- A collaborative evaluation of programs to prepare highly qualified teachers / Patricia Yee, Andrea Nee, Kamal Hamdan.
Includes index.
Print version record
Keywords: Education -- Leadership; Education -- General; Education; Educational leadership; School management and organization